2014 15th International Radar Symposium (IRS) 2014
DOI: 10.1109/irs.2014.6869307
|View full text |Cite
|
Sign up to set email alerts
|

ISAR imaging of ground targets with an X-band FMCW Radar system for airport surveillance

Abstract: Within the European project SOS ("Sensors system for detection and tracking of dangerous materials in order to increase the airport security in indoor landside area") new solutions for airports' security are being studied by several European universities and industries. In particular, a collaborative effort is devoted to the development of an imaging mode for the airports' perimeter surveillance, the results of which will be preliminarily shown in this paper. An X-band frequency modulated continuous wave (FMCW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…However, with the increasing demand for finer image resolution, the accuracy requirement of error compensation for radar imaging has also increased. Besides, the distance between radar and target for some applications are becoming smaller, for example, target detection and ranging for autonomous vehicles, harbor surveillances, and airport security checks [21][22][23]. In these situations, termed near-field ISAR imaging, the plane wave assumption may not be accurate enough for high-resolution ISAR imaging and the corresponding image quality would be degraded.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increasing demand for finer image resolution, the accuracy requirement of error compensation for radar imaging has also increased. Besides, the distance between radar and target for some applications are becoming smaller, for example, target detection and ranging for autonomous vehicles, harbor surveillances, and airport security checks [21][22][23]. In these situations, termed near-field ISAR imaging, the plane wave assumption may not be accurate enough for high-resolution ISAR imaging and the corresponding image quality would be degraded.…”
Section: Introductionmentioning
confidence: 99%
“…In [4]- [5] the activities of SAPIENZA University of Rome and MetaSensing BV were jointly focused on the development of solutions for the surveillance of the airport's external area perimeter, in order to prevent threats from people or vehicle that are usually moving around the airport. In particular, the results showed that the X-band frequency modulated continuous wave (FMCW) radar sensor developed at MetaSensing could be used for detection, tracking and imaging of possible threats.…”
Section: Introductionmentioning
confidence: 99%